2021
DOI: 10.1039/d1ra07534a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diluent on the extraction of europium(iii) and americium(iii) with N,N,N′,N′-tetraoctyl diglycolamide (TODGA)

Abstract: Solvent extraction of Eu3+ and Am3+via N,N,N′,N'-tetraoctyl diglycolamide (TODGA) dissolved in different molecular diluents was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Moreover, Huang et al have also reported 1:1 complex for the extraction of trivalent ions in kerosene, whereas Bhattacharyya et al, reported the formation of the 1:2 complex for the same ligand in the 20% isodecanol + 80% n -dodecane system . The effect of diluents on the stoichiometry of the extracted species for trivalent ion extraction by TODGA is also reported …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, Huang et al have also reported 1:1 complex for the extraction of trivalent ions in kerosene, whereas Bhattacharyya et al, reported the formation of the 1:2 complex for the same ligand in the 20% isodecanol + 80% n -dodecane system . The effect of diluents on the stoichiometry of the extracted species for trivalent ion extraction by TODGA is also reported …”
Section: Resultsmentioning
confidence: 96%
“…30 The effect of diluents on the stoichiometry of the extracted species for trivalent ion extraction by TODGA is also reported. 67 The TP formation is undesirable phenomenon in the extraction of tetravalent metal ions, and hence, the solvent extraction conditions are generally optimized to prevent it. It is always better to have a solvent system which can dissolve the maximum amount of metal ions at the desired acidity without any TP formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As a result, the role of 1-alcohols in these systems has been attributed to solvation of the Ln-DGA complex through interactions with the outer-sphere hydrogen bonding network. 3,25…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanides (Lns), which make up the 4f period, exhibit unique electronic properties that make them of interest for many applicationsincluding digital technology, catalytic converters, phosphors, lasers, permanent magnets, and ceramics. [1][2][3] With the vast array of applications comes the need for an abundance of Lns; however, the current worldwide shortage of Lns creates a supply-demand risk, where industrial product cannot meet the demand. 1 Currently, trivalent Lns are recovered from ores through a hydrometallurgical process involving the dissolution of the ore in high concentrations of acid, where the Lns are recovered and separated via solvent extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation